IMPLEMENTASI PUTUSAN PEMIDANAAN DAN PENUNTUTAN OLEH HAKIM DALAM SISTEM PERADILAN PIDANA - TEGAR HARBIYANA PUTRA; ADHIPUTRO PANGARSO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
The number of sentencing decisions that are lighter than the demands of the public prosecutor seem to have been taken for granted which does not need to be debated anymore. And this tendency does not only occur in criminal cases in general courts, but also occurs in special courts such as the court for corruption, which in some decisions the sentence also tends to be lighter than the demands of the public prosecutor from the commission for eradicating corruption. In this study, data collection methods are needed to assist in the research process, so the researcher uses the library method or literature study. Literature study is a data collection procedure by reading, understanding, and citing data sources in the form of primary legal materials, secondary and tertiary legal materials that are relevant to the problems to be researched and discussed. The phenomenon of sentencing decisions which tend to be lighter than the demands that give rise to various implications is caused by various factors, including the lack of commensurate quality and quantity of human resources and facilities and infrastructure in court with the large workload of the court and the mention of the name of the criminal period in the psychologically charged prosecution. has influenced and directed judges in determining the criminal period to be decided, besides that it is not uncommon for judges to be incomplete in elaborating aggravating matters and mitigating matters to themselves and the actions of the accused in their decisions, and deciding sentences that are lighter than the demands. It was also deliberately carried out by the judge with the rationale of realizing a balance between the demands and the defense of the defendant.